Species-distinctiveness in the vocal behaviour of six sympatric bulbuls (genus Pycnonotus) in South-East Asia - Somboon Kamtaeja (2018)
Bulbuls (Passeriformes:Pycnonotidae) are a biodiverse group of birds that produce a variety of vocalisations, yet the vocal behaviour of most bulbuls has not been formally described or the subject of bioacoustical study. We present the first detailed descriptions of the song and singing behaviours of six species of bulbul in the genus Pycnonotus, based on recordings of birds in mixed-species flocks in the tropical forests of northern Thailand. All six species are frugivores that often forage together in the same fruiting tree. We compared nine fine structural features of the songs of these species to understand the vocal behaviour of each and the potential importance of vocalisations in species recognition in these mixed-species flocks. Our analyses reveal substantial differences in the structure of songs as well as marked differences in singing behaviour between species. Discriminant function analysis readily distinguishes the songs of the six species based on structural differences. Discriminant function analysis of species with the most similar plumage features (as assessed by human observers) readily distinguishes between phenotypically similar pairs of congeners. Our results provide evidence that vocalisations may be important in species recognition and as species-isolating mechanisms between closely related and sympatric Pycnonotus bulbuls. The species-typical features described here may be helpful to biologists and conservationists, particularly as several species of bulbul are of conservation concern. © 2012 BirdLife Australia.